Braving the zero-leverage unknown : post-crisis performance and credit dynamics of portuguese firms - Garcês, Bernardo Jorge (2022)
Debt is not as ubiquitous as classical theories of capital structure would like you to believe. A sizeable slice of firms have no debt in their balance sheets, a phenomenon termed the zeroleverage puzzle. We investigate the performance and credit dynamics of such firms, private and public, in the recovery period following the Sovereign Debt Crisis in Portugal; and conciliate our findings with existing hypotheses on the drivers of this behavior. Our results suggest that zero-leverage firms outperform their unlevered counterparts, namely when conditioning on dividend-paying status. Attesting to the persistence of debt aversion, we find that zero-leverage firms are also likelier to follow a conservative debt policy up to eight years after the zeroleverage event. In aggregate, we extract robust evidence in favor of strategic considerations as the driving force behind firms’ hesitancy to take on debt – a boon for the financial flexibility hypothesis. Conversely, the financial constraint hypothesis finds limited support in our data.